(untitled) (The Shivapuri Journal, 2025)
Local forces can be an effective tool in counterinsurgency provided they are well regulated and used in a just manner. They can contribute to the security sector, as well as developing wartime social order and government legitimacy at the local level. To the contrary, in the Nepal insurgency, local forces were branded predatory by human rights activists and civil society, hence could not gain the political support necessary for their mobilization. Despite spontaneous self-defense uprisings by the people, use of local forces never came into being as a security and social tool of counterinsurgency. Cause-oriented groups generally target local forces existence; however, their legitimate use through a well-worked out mobilization plan results in effective counterinsurgency.